Changing trends in cancer incidence of upper aerodigestive tract and stomach in Japanese alcohol‐dependent men (1993‐2018). (3rd December 2019) - Yokoyama, Akira; Omori, Tai; Yokoyama, Tetsuji
Abstract: Background: Esophageal squamous cell carcinoma (ESCC), head and neck SCC (HNSCC), and gastric adenocarcinoma (GA) are frequently detected at an early stage using endoscopic screening in Japanese alcohol‐dependent men. Methods: We performed endoscopic screening with esophageal iodine staining and oropharyngolaryngeal inspection in 7582 Japanese alcohol‐dependent men (40‐79 years) during 1993‐2018, and retrospectively investigated their initial screening results. Results: The 2008‐2018 screening showed lower detection rates for ESCC (2.6% vs 4.0%, P  = .0009) and GA (0.5% vs 1.4%, P  < .0001) for all age brackets, compared with the 1993‐2007 screening. The HNSCC detection rate did not change (1.0% vs 1.1%). Multiple logistic regression analyses showed that the 2008‐2018 screening had a reduced OR (95% CI) for ESCC (0.34 [0.25‐0.47]) and GA (0.19 [0.10‐0.35]), compared with the 1993–2007 screening. The reduction in H pylori infection is probably the main reason for the decrease in GA detection over time. Declining trends in pack‐years and gastric atrophy and increasing trends in age and body mass index (BMI) were found over time. The presence of advanced gastric atrophy increased the risk for ESCC as well as GA. The inactive heterozygous aldehyde dehydrogenase‐2*1/*2 genotype was a strong risk factor for ESCC, HNSCC, and GA. Fewer pack‐years and a larger BMI decreased the ESCC risk. However, these confounders cannot fully explain why the incidence of ESCC has decreased markedly over the recent decade. Conclusions: The detection rates of ESCC and GA have markedly decreased during the past decade in the alcohol‐dependent population. The enigmatic declining trend of ESCC warrants research on this topic. Abstract : Comparison of detection rates of esophageal squamous cell carcinoma (ESCC) and gastric adenocarcinoma (GA) according to age groups and ALDH2 genotype between the 1993‐2007 screening period and the 2008‐2018 screening period in Japanese alcohol‐dependent men. The detection rates for ESCC and GA were consistently lower during the 2008‐2018 study period than during the 1993‐2007 study period regardless of age groups and ALDH2 genotype.